Restorative Justice As A Reason For Termination Of Investigations On Criminal Acts Of Hurt Or Destruction In The Electronic Information And Transaction Law - Su'udi SU'UDI (Indonesia Strategic Sustainability, 2022)
The implementation of restorative justice in the criminal justice system should be carried out comprehensively, considering criminal decisions have only been retaliation and condolences so far. Only sad decisions ultimately lead to overcapacity in correctional institutions. As in the case of defamation, initially, this defamation was only regulated in Article 310 of the Criminal Code (KUHP), which in essence, contains the prohibition against attacking honor, slandering, and defaming someone in written form. And pictures. However, over time, defamation regulation is also regulated in Law Number 19 of 2016 concerning Information and electronic transactions, commonly known as the ITE Law. Furthermore, Circular Letter (SE) No. SE/2/11/2021 concerning Ethical Cultural Awareness to Create a Clean, Healthy, and Productive Digital Space for Indonesia. The statement in the SE stated that the National Police has the principle that criminal law is a last resort (ultimum remidium) and always prioritizes and seeks restorative justice in existing cases, including termination of investigations. The type of research used in this research is normative juridical research, this type of research is research that refers to legal norms and rules in its study. The results of this study are to understand the restorative justice arrangement as a reason for stopping the investigation and the role of the investigator in carrying out mediation in defamation cases regulated in the ITE Law.